A comparative analysis of MAIDS and ISO13232 databases for the identification of the most representative impact scenarios for powered 2-wheelers in Europe. (3rd October 2018) - Grassi, Alessandro; Baldanzini, Niccolò; Barbani, Daniele; Pierini, Marco
Abstract: Objective: The ISO13232 standard provides guidelines and methodologies for research on the effectiveness of protective devices fitted to motorcycles. The accident database used to develop the standard was composed of 2 data sets from Hannover and Los Angeles, dating from 1996. This study aims to apply the methodology outlined in the standard to a more recent European accident database to determine whether the set of the 7 most relevant impact configurations identified in the ISO13232 are representative of the European context. Methods: The ISO13232 database was rebuilt from the data tables attached to the standard and processed according to the procedure described in ISO13232-Part 2, to ensure reproducibility of the results. The comparison data set was extracted from the Motorcycle Accidents In-Depth Study (MAIDS) database. Data were then coded, processed, and analyzed using the ISO13232 methodology. To eliminate any subjectivity in the selection process of the configurations, a new ranking criterion (configuration risk index, CRI) was implemented. The CRI combined the evaluation of an accident configuration's frequency of occurrence and its harmfulness. Results: Comparison of the frequency ranking of the impact configurations from the 2 databases revealed some notable differences. Five of the 10 most important configurations were common to both databases, although ranking order differed. CRI-based selection led to differences in ranking orders. The CRI allowed better identification of the most important configurations and it was employed to define the proposed new set of configurations. Conclusion: A new set of 7 accident configurations was defined by applying the ISO13232 procedure to the MAIDS data and ranking the results with a newly proposed method. The final set had only one configuration in common with those defined in the ISO13232, testifying to the importance of defining an updated and more representative set of configurations for the European context.